2015
DOI: 10.1002/2014jb011556
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of a Strombolian eruption: Inferences from particle data recorded with thermal video

Abstract: Over the past decade, a proliferation of new technologies has pushed forward our ability to measure the dynamics of volcanic emissions as they exit, and ascend above, the vent. Measuring parameters of all particles as they exit the vent during an explosive eruption is the best way to gather parameters such as size, shape, velocity, and mass for the solid (particulate) fraction of the plume, in our case this being the lapilli and bomb component. We compute particle velocities and size distributions using high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…An individual Bexplosion^is characterized by multiple, second-long Bpulses^and sub-second-long Bsubpulses^, each pulse being characterized by the ejection of particles at similar velocities which then decrease in time (Taddeucci et al 2012a;Gaudin et al 2014;Bombrun et al 2015). In addition we can observe multiple emission points during a single event.…”
Section: Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…An individual Bexplosion^is characterized by multiple, second-long Bpulses^and sub-second-long Bsubpulses^, each pulse being characterized by the ejection of particles at similar velocities which then decrease in time (Taddeucci et al 2012a;Gaudin et al 2014;Bombrun et al 2015). In addition we can observe multiple emission points during a single event.…”
Section: Terminologymentioning
confidence: 99%
“…James et al 2004James et al , 2006James et al , 2008Lane et al 2013), and field observations (e.g. Chouet et al 1974;Blackburn et al 1976;Ripepe et al 1993Ripepe et al , 2005Patrick et al 2007;Harris et al 2012;Taddeucci et al 2012a, b;Gaudin et al 2014;Bombrun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For decades, this area has also been used for volcano imaging studies. For instance, thermal infrared cameras have been used both to study the rise velocity of eruption plumes and to characterize explosion phases based on the coupling or decoupling of pyroclasts with the gas phase, also drawing inferences on the density of the gas phase [ Patrick , ; Harris et al ., ; Bombrun et al ., ]. High‐speed, visible light cameras are well suited for tracking individual pyroclasts, allowing one to relate their ejection velocity, size, and angle to the dynamics and energetics of pressure release in the volcanic conduit [ Gaudin et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with other studies, metric-size ballistic projectiles are not typical of Strombolian and Sub-Plinian activity and are more common during Vulcanian explosions [Maeno et al 2013;Bombrun et al 2015;Taddeucci et al 2017]. Based on the size/velocity inverse relationship [Bombrun et al 2015], the maximum launching velocities observed for metric-size projectiles at Tungurahua are higher than those expected for Strombolian activity (<100 m s −1 for >0.6-m-diameter blocks) with velocities up to 117-135 m s −1 , 143-162 m s −1 and 144-153 m s −1 for January, May-June and November eruptions respectively. The launching velocities are also similar to literature data on Vulcanian eruption (100-400 m s −1 ) [Druitt et al 2002;Maeno et al 2013].…”
Section: Eruptive Style and Hazard Assessmentmentioning
confidence: 77%
“…Despite a relatively straightforward approach, ballistic projectile hazard assessment is not systematic, one of the main issue being the acquisition of field data [Taddeucci et al 2017]. High-speed cameras (visible and infrared) and volcanic radars provide new insights on projectiles and gas escape velocity at the vent as well as in flight dynamics [Gouhier and Donnadieu 2008;Taddeucci et al 2012a;Bombrun et al 2015]. Nevertheless most of these studies are realized on a limited number of laboratory volcanoes with mostly low-explosive dynamics.…”
Section: Introductionmentioning
confidence: 99%